The effect of psychological capital and self-leadership on work engagement among agricultural extension advisors - Green, Kirsty (University of the Free State, 2001)
Work engagement is considered highly important to organisations and within the field of industrial psychology as organisations hope to improve and increase employee’s engagement and in so doing, enhance employees’ performances. Focus has shifted in organisations to proactively recognise how the concepts of positive psychology, psychological capital, and self-leadership, can promote the improvement of work engagement in employees. The present research studied the effect of psychological capital and self-leadership on the work engagement levels of agricultural extension advisors within South Africa. The main objective of the study was to explore whether psychological capital and self-leadership had a significant effect on the work engagement of agricultural extension advisors. The second objective of the study was to assess whether there was a distinction between male and female agricultural extension advisors concerning their levels of work engagement. A quantitative research method was used in which data was gathered using three scales (UWES, PCQ-24 and combination of the ASLQ and RSLQ). Cronbach’s alphas were used to measure the reliability of the scales and based on this all constructs were determined to be valid and reliable measures. A list of respondents was provided by the South African Society for Agricultural Extension and emails were sent out to the respondents containing the questionnaires. A total of 103 viable questionnaires were attained. A Pearson product-moment correlation analysis and stepwise multiple regression analysis was used to address the main objective. Both psychological capital (r = .721, p = .000) and self-leadership (r = .585, p = .000) had significant positive correlation with work engagement that were both interpreted as large, substantial relationships. The stepwise multiple regression analysis results indicated that three important predictors of work engagement were hope, optimism and behaviour-focused strategies which explained 62.8% of the variance in work engagement. Hope was shown to have the highest contribution (R2 = 0.52) as hopeful employees have shown to be goal directed and have positive outlooks that lead to positive behaviours that enable work engagement of employees. The secondary objective was addressed using an independent sample t-test; however, the levels of work engagement between male and female agricultural extension advisors were found to be insignificant indicating that there were no differences. Conclusions from the study indicated that personal and work resources from psychological capital and self-leadership influence the work engagement levels of employees. Therefore, self-leadership strategies should be used to lay the foundation for organisations to create positive change and expand the positive psychological resources of employees to increase the work engagement levels. It was further recommended that psychological capital be used to enhance employees’ experiences of hope and optimism by including them in employees training and development initiatives. Future studies should focus on more advanced research of these concepts within the agricultural sector to help agricultural extension advisors to develop and increase their levels of work engagement.
Dissertation (M.Com.(Industrial Psychology))--University of the Free State, 2021
Keywords: Work engagement; Psychological capital; Self-leadership; Agricultural extension advisors